PENDAMPINGAN GAPOKTAN MITRA ARJUNA DALAM MEMPROMOSIKAN PRODUK HASIL OLAHAN PERTANIAN - Ali Roziqin; Eko R. P Widodo; Syasya Y. F Mas'udi (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
Batu City is known as one of the apple producing areas, but lately apple products are increasingly being abandoned by farmers due to difficulty in maintenance and falling market value. Based this statement, some farmers switch to growing vegetables and rely on processed products to market their products. This service aims to assist the farming community in Tulungrejo village to strengthen the local economy through assistance in promoting agricultural processed products. This assistance is carried out by cooperating with Gapoktan partners, Mitra Arjuna, through a lecturer partner service scheme. This service has succeeded in attracting public attention through promotions carried out by the service through Instagram, YouTube and TikTok. This has resulted in more and more processed products such as apple chips, cauliflower, chilies, pineapples, broccoli, and peppers that are known and sold well in the wider community. This assistance received positive feedback from the manager of the Mitra Arjuna Gapoktan and hopes that this service will last for multi-years. The assistance provided can also be specified for certain farmer groups so that the goal of improving the local economy, especially the farmers in Tulungrejo village, can be realized.